2020
DOI: 10.1590/2175-8239-jbn-2019-0188
|View full text |Cite
|
Sign up to set email alerts
|

Association between interleukin-6 gene polymorphism and iron regulation in hemodialysis patients infected with HCV

Abstract: Backgrounds: Hepcidin is related to the pathogenesis of chronic renal failure anemia, which is considered a chronic inflammatory state as well as HCV infection. IL-6 stimulates the release of hepcidin from the liver, suppresses intestinal iron uptake, and releases iron from internal stores. Method: To detect the association between IL-6 gene polymorphism and anemia markers, 80 hemodialysis (HD) patients [40 negative HCV HD patients and 40 positive HCV HD patients] were studied by routine chemistry and complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…IL6 rs1800796 SNP was associated with kidney function and CKD prevalence in a large Japanese population [ 19 ]. Ali et al reported that the IL6 −597 G/A (rs1800797) as well as the −174 (rs1800795) G/C polymorphisms may play a role in susceptibility to hepatitis C virus infection among Egyptian hemodialysis patients [ 40 ]. A meta-analysis revealed that IL6 rs1800795, rs1800796, and rs1800797 SNPs are important players in diabetic nephropathy development [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL6 rs1800796 SNP was associated with kidney function and CKD prevalence in a large Japanese population [ 19 ]. Ali et al reported that the IL6 −597 G/A (rs1800797) as well as the −174 (rs1800795) G/C polymorphisms may play a role in susceptibility to hepatitis C virus infection among Egyptian hemodialysis patients [ 40 ]. A meta-analysis revealed that IL6 rs1800795, rs1800796, and rs1800797 SNPs are important players in diabetic nephropathy development [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Certain polymorphisms influence interleukin-6 levels [ 6 ]. The IL-6 production levels have been controlled precisely at the transcriptional and translational levels [ 7 ]. The IL-6 gene polymorphisms are designated to consist of regulation at the transcriptional stage, e.g., the (−174G/C) polymorphism [ 8 ], the (−597G/A) polymorphism, and the (−572G/C) polymorphism.…”
Section: Introductionmentioning
confidence: 99%